Pembelajaran Ilmu Pengetahuan Sosial Berbasis Kearifan Lokal di SMP Negeri 18 Kota Bengkulu - Muhammad Rizaldi Ardian; Desy Eka Citra Dewi; Sepri Yunarman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the implementation of Social Studies (IPS) learning based on local wisdom in the eighth grade of SMP Negeri 18 Bengkulu City. The research is grounded in the urgency of contextual education that emphasizes not only cognitive aspects but also the development of student character through social and cultural values embedded in the community. A qualitative research method with a case study approach was employed. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model consisting of data reduction, presentation, and conclusion drawing. The findings reveal that integrating local wisdom, particularly the Tabot and Sedekah Laut traditions as well as the use of the Bengkulu language in daily communication, makes Social Studies learning more contextual, meaningful, and relevant. The values embedded—such as responsibility, cooperation, tolerance, politeness, and respect for cultural heritage—contribute significantly to strengthening character education. Key supporting factors include teacher competence in developing pedagogical strategies, the availability of school facilities, and a supportive learning environment. Furthermore, teachers’ experiences and school policies that prioritize local culture reinforce the integration of local wisdom into the curriculum. This study underscores that local wisdom–based Social Studies learning is not only relevant for enriching instructional materials but also strategic in preserving regional culture while fostering a generation that is character-driven, critical, and globally minded without losing connection to national cultural roots. Thus, contextualized learning through local wisdom provides a sustainable educational model that bridges tradition and modernity, equipping students with both cultural identity and global perspectives.